Adjunctive counseling during brief and extended buprenorphine-naloxone treatment for prescription opioid dependence: a 2-phase randomized controlled trial. - Weiss, Roger D; Potter, Jennifer Sharpe; Fiellin, David A; Byrne, Marilyn; Connery, Hilary S; Dickinson, William; Gardin, John; Griffin, Margaret L; Gourevitch, Marc N; Haller, Deborah L; Hasson, Albert L; Huang, Zhen; et al. (Archives of general psychiatry, 2011)
No randomized trials have examined treatments for prescription opioid dependence, despite its increasing prevalence.
Keywords: Adult; Buprenorphine; Combined Modality Therapy; Counseling; Drug Therapy, Combination; Female; Humans; Interview, Psychological; Male; Naloxone; Narcotic Antagonists; Opiate Substitution Treatment; Opioid-Related Disorders; Psychiatric Status Rating Scales; Treatment Outcome